Exploring suicidal behaviours by probation clients—a qualitative near-lethal study. (4th February 2017) - Mackenzie, J C; Cartwright, T; Borrill, J
Abstract: Background: Existing research emphasizes that offenders serving community based sentences are at an increased risk of suicide compared with the general population, however, there is little understanding about the causes of this risk. The aim of the current research was to understand how to support probation clients and prevent suicide, by exploring the experiences of probation clients who carried out near-lethal suicide attempts whilst under probation supervision. Methods: In-depth interviews were carried out with seven probation clients who made near-lethal suicide attempts whilst serving a probation sentence. Data were analysed using Interpretative Phenomenological Analysis. Results: Participants recounted negative experiences which they perceived to be linked to their suicidal feelings and behaviours, such as experiencing bereavements, perceived loss of control over their mental state or situation, and difficulties relating to stages of their probation sentence. Participants expressed severe difficulties with trusting authorities, making disclosure of suicidal feelings problematic. However, participants emphasized the role that purposeful and meaningful activity can play in suicide prevention. Conclusions: Suicide prevention strategies must be tailored to the needs of probation clients across the UK. Mandatory training for probation staff is recommended to help reduce suicides, and support from external agencies should be sought where possible.